Experiências vivenciadas pelas parturientes: enfoque sócio cultural - Bezerra, Maria Gorette Andrade (2004)
The childbirth is a relevant happening in a womarTs life once it is an unique moment to the mother-son binomial and it is surrounded by myths and beliefs. This study aimed at understanding the factors that interfere in experience lived by pregnant women. 07 (seven) women, who live in Fortaleza - Ceará and had their children in a public maternity school, in June, July and August, 2003, took part into the study. The research method used was the Ethno-nursing, applying the models Observation-participation and reflection (OPR) and the Stranqe-friend. A script was used as an instrument for data collection and it contained data which were observed in the Admittance Unit and in the Obstetric Center, a semi-structured interview, which was recorded and transcribed thoroughly by the researchers, in the first month of the puerperal period; in a note’s diary. The findings were reflected and based on the Cultural Care’s Diversity and Universality Theory, by Madeleine Leininger, which showed multiple factors that influence the pregnant women’s behavior. By the depositions’ analysis, 5 (five) large themes appeared, being them divided into categories such as: theme I Vision of the childbirth, categories by having influenced the gestation period; the family, the friends, the school and the prenatal influencing the pregnancy process and the means of communication, theme II the presence of fear in the pregnancy and childbirth process categories friends’ information and the institution’s dynamics. Theme III living the pregnancy, categories social and metabolic factors as determiners of the pregnanfs behavior and the unexpected pregnancy, theme IV religiousness categories the influence of beliefs and religiousness in the childbirth, theme V institutional attendance categories the prenatal and the childbirth in the maternity. Before the results, enhancement in public health’s policies were suggested in order to fulfill women’s and their family members’ necessities, reorientating the attendance and emphasizing the clientele’s culturai values.